Exposure to vinyl chloride monomer: results of a cohort study after a seven year follow up. The French VCM Group. - Laplanche, A (1992)
In 1980 a prospective cohort study of exposed and non-exposed subjects was initiated in France by the Institut National de la Santé et de la Recherche Médicale (INSERM U287) in collaboration with occupational physicians from the companies involved. The aim was to evaluate the association between mortality and cancer morbidity and occupational exposure to vinyl chloride monomer (VCM). A total of 1100 subjects exposed to VCM and 1100 non-exposed controls matched for age (to two years), plant, and physician were followed up for seven years (8299 and 8202 person years for exposed subjects and controls respectively) for vital status and health and occupational state. Forty deaths occurred among exposed and 43 among non-exposed subjects (relative risk (RR) = 1.0; 95% confidence interval (95% CI) 0.6-1.5). Forty eight and 32 cases of cancer were reported among exposed and non-exposed subjects, respectively (RR = 1.3; 95% CI 0.8-2.1). Three cases of angiosarcoma of the liver occurred in the exposed group. Eight cases of lung cancer occurred among exposed subjects and six among non-exposed subjects. Fourteen cases of Raynaud's disease were found among exposed and one among non-exposed subjects and the difference was significant. One hundred and twenty three and 93 cases of cardiovascular disease (Raynaud's disease excluded) occurred in the exposed and non-exposed groups respectively (RR = 1.4; 95% CI 1.0-1.8); this difference was mainly due to hypertension. The test for an increasing risk with increased exposure was significant. The percentages of diseases of the respiratory system did not differ between the two groups (RR = 1.1; 95% CI 0.7-1.8).